Bio and necropolitical portraits in the 35mm negatives of the Hermanos Mayo: Approaches to a vitiated and vagabond masculinity in the urban daily life of contemporary Mexico - Hernández Castillo, Diana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Through the intersection between visual culture and the humanities (specifically history), I intend to analyze the 35mm negatives of the photographs taken by the Hermanos Mayo of a male individual who was naked and drugged on a main avenue in Mexico City in 1971. We will investigate how it was observed and exposed in an urban space where pedestrians and bystanders became spectators of said event. These spectators, stopping to contemplate and apprehend the drug addict, formed a specific urban microspace to corral him and expose him to death. That is, they built an uninhabitable space within the habitable.